Comparison of biomechanical characteristics of rowing performance between elite and non-elite scull rowers: A pilot study - Kim, J.-S.; Cho, H.; Han, B.-R.; Yoon, S.-Y.; Park, S.; Cho, H.; Lee, J.; Lee, H.-D. (Korean Journal of Sport Biomechanics, 2016)
Objective: This study aimed to examine the characteristics of joint kinematics and synchronicity of rowing motion between elite and non-elite rowers. Methods: Two elite and two non-elite rowers performed rowing strokes (3 trials, 20 strokes in each trial) at three different stroke rates (20, 30, 40 stroke/min) on two stationary rowing ergometers. The rowing motions of the rowers were captured using a 3-dimensional motion analysis system (8-infrared camera VICON system, Oxford, UK). The range of motion (RoM) of the knee, hip, and elbow joints on the sagittal plane, the lead time (TLead) and the drive time TDrive) for each joint, and the elapsed time for the knee joint to maintain a fully extended position (TKnee) during the stroke were analyzed and compared between elite and non-elite rowers. Synchronicity of the rowing motion within and between groups was examined using coefficients of variation (CV) of the TDrive for each joint. Results: Regardless of the stroke rate, the RoM of all joints were greater for the elite than for non-elite rowers, except for the RoMs of the knee joint at 30 stroke/min and the elbow joint at 40 stroke/min (p < .05). Although the TLead at all stroke rates were the same between the groups, the TDrive for each joint was shorter for the elite than for the non-elite rowers. During the drive phase, elite rowers kept the fully extended knee joint angle longer than the non-elite rowers (p < .05). The CV values of the TDrive within each group were smaller for the elite compared with non-elite rowers, except for the CV values of the hip at all stroke/min and elbow at 40 stroke/min. Conclusion: The elite, compared with non-elite, rowers seem to be able to perform more powerful and efficient rowing strokes with large RoM and a short TDrive with the same TLead.